2010
DOI: 10.1242/dev.037812
|View full text |Cite
|
Sign up to set email alerts
|

Sall1-dependent signals affect Wnt signaling and ureter tip fate to initiate kidney development

Abstract: SUMMARYDevelopment of the metanephric kidney depends on precise control of branching of the ureteric bud. Branching events represent terminal bifurcations that are thought to depend on unique patterns of gene expression in the tip compared with the stalk and are influenced by mesenchymal signals. The metanephric mesenchyme-derived signals that control gene expression at the ureteric bud tip are not well understood. In mouse Sall1 mutants, the ureteric bud grows out and invades the metanephric mesenchyme, but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 51 publications
6
43
1
Order By: Relevance
“…1E); therefore, it may serve as the signal to the CM that promotes unrestrained differentiation. Consistent with this notion, constitutively active β-catenin expressed in CM results in ectopic RV formation, indicating that at high levels this signal is sufficient for nephron induction (Kiefer et al, 2010;Park et al, 2012). Our previous studies showed that increased levels of Wnt9b, similar to those observed in Sall1 mutants (Kiefer et al, 2010) (Fig.…”
Section: Research Articlesupporting
confidence: 75%
See 3 more Smart Citations
“…1E); therefore, it may serve as the signal to the CM that promotes unrestrained differentiation. Consistent with this notion, constitutively active β-catenin expressed in CM results in ectopic RV formation, indicating that at high levels this signal is sufficient for nephron induction (Kiefer et al, 2010;Park et al, 2012). Our previous studies showed that increased levels of Wnt9b, similar to those observed in Sall1 mutants (Kiefer et al, 2010) (Fig.…”
Section: Research Articlesupporting
confidence: 75%
“…Consistent with this notion, constitutively active β-catenin expressed in CM results in ectopic RV formation, indicating that at high levels this signal is sufficient for nephron induction (Kiefer et al, 2010;Park et al, 2012). Our previous studies showed that increased levels of Wnt9b, similar to those observed in Sall1 mutants (Kiefer et al, 2010) (Fig. 1E), was sufficient to increase expression of the RV genes Wnt4, Fgf8 and Pax8; yet this level of Wnt9b expression did not induce ectopic RVs (Kiefer et al, 2012).…”
Section: Research Articlesupporting
confidence: 72%
See 2 more Smart Citations
“…Within nephrogenic mesenchyme, expression of the Wt1 transcription factor is essential for mesenchyme survival, whereas Six2 is crucial for self-renewal and is required to suppress the premature differentiation of nephron progenitor cells (Kobayashi et al, 2008;Kreidberg et al, 1993;Self et al, 2006). Eya1, which lies upstream of Six2, is necessary for induction of the mesenchyme (Kiefer et al, 2010;Nishinakamura et al, 2001;Xu et al, 1999). Genetic inactivation of Bmp7, which is expressed both in cap mesenchyme and ureteric bud tissue, results in reduced proliferation and premature depletion of nephron progenitor cells (Blank et al, 2009;Dudley et al, 1995;Luo et al, 1995).…”
Section: Introductionmentioning
confidence: 99%